The complete guide to film and digital production : the people and the process - Wales, Lorene M. (New York, NY : Routledge, 2024)
"This fully revised fourth edition offers a comprehensive introduction to the roles, procedures, and logistics of the film and digital video production process. Author Lorene M. Wales takes the reader from development and pre-production all the way to post-production, marketing and distribution, offering a hands-on approach suitable for projects of any budget and scale, explaining every stage and key role in the life of a film. Focusing on how key roles shape the film production process, Wales guides filmmakers through the A-Z of making a film in today's industry and draws from insights and experiences from working filmmakers throughout. The book is practically focused and includes a wealth of sample checklists, schedules, accounting paperwork, and downloadable forms and templates for practical use. The fourth edition has been fully revised and updated to include a new chapter on how to break into the industry, expanded and updated sections on distribution (including theatrical and streaming platforms), set safety, colour grading, and legal matters, as well as updated insights from a diverse range of industry professionals. This is the ideal text for Undergraduate students studying entry-level film and video production, producing and cinematography, along with aspiring and working professionals in film and digital production. The updated companion website includes video tutorials, a personnel hierarchy, a guide to mobile apps useful during production, PowerPoints for instructor use, and a complete set of sample production forms and templates for download, including schedules, accounting paperwork, releases, and production checklists"--Provided by publisher.
includes bibliographical references and index.
Keywords: Motion pictures -- Production and direction